Rewealthization in 21st century Western countries: The defining trend of the socioeconomic squeeze of the middle class - Louis Chauvel; Eyal Bar Haim; Anne Hartung; Emily Murphy (Luxembourg Income Study (LIS), 2021)
Over the last three decades, the wealth-to-income ratio (WIR) in many Western countries, particularly in Europe and North America, increased by a factor of two. This represents a defining empirical trend: a rewealthization (from the French repatrimonialisation) - or the comeback of (inherited) wealth primacy since the mid '90s. For the sociology of social stratification, 'occupational classes' based on jobs worked must now be understood within a context of wealth-based domination. In this paper, we first illustrate important empirical features of an era of rising WIR. We then outline the theory of rewealthization as a major factor of class transformations in relation to regimes stabilized in the post-WWII industrial area. Compared to the period where wealth became a secondary resource for a middle-class lifestyle afforded by education and labor income for both men and women, rewealthization has steepened the vertical climb to resource 'abundance' (feng) in society while masking social reproduction.
Keywords: 330; inequality; middle-class society; repatrimonialisation; wealth-to-income ratio